2011
DOI: 10.1093/infdis/jir508
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Anabolic and Catabolic Processes May Contribute to Alcohol-Accentuated SAIDS-Associated Wasting

Abstract: These data suggest negative modulation of insulin signaling coupled with enhanced Ub-proteasome system activity may be central mechanisms underlying chronic binge alcohol-induced accentuation of SIV-associated muscle wasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 34 publications
5
46
0
Order By: Relevance
“…As supported by our study and other similar studies, catabolic and metabolic dysregulation are central mechanisms underlying the role of alcohol in accentuation of muscle wasting at end-stage disease in simian immunodeficiency virus (SIV)-infected animals (LeCapitaine et al, 2011, Lang et al, 2009, Molina et al, 2008). However, additional mechanisms might also contribute to loss of muscle mass resulting from chronic alcohol abuse and or HIV/AIDS.…”
Section: Introductionsupporting
confidence: 82%
“…As supported by our study and other similar studies, catabolic and metabolic dysregulation are central mechanisms underlying the role of alcohol in accentuation of muscle wasting at end-stage disease in simian immunodeficiency virus (SIV)-infected animals (LeCapitaine et al, 2011, Lang et al, 2009, Molina et al, 2008). However, additional mechanisms might also contribute to loss of muscle mass resulting from chronic alcohol abuse and or HIV/AIDS.…”
Section: Introductionsupporting
confidence: 82%
“…Our previous studies demonstrated that CBA administration to SIVinfected macaques results in significantly accentuated skeletal muscle inflammation preceding overt manifestations of alcoholic myopathy (25). In addition, we showed accentuated skeletal muscle wasting at end-stage SIV infection (24), which we later reported is characterized by marked dysregulation of ubiquitin proteasome components, increased skeletal muscle proteasomal activity, and attenuation of anabolic pathways (21). However, the possibility that the inflammatory/oxidative milieu could impact SC function and contribute to the observed accentuated wasting in CBA-administered SIV-infected macaques had not been previously examined.…”
Section: Discussionsupporting
confidence: 53%
“…These cells are quiescent during adulthood but can enter into cell cycle upon stimulation to repair damaged muscle by proliferation, differentiation, and fusion with existing myofibers (39). Our previous studies with chronic binge alcohol (CBA)-fed, Simian immunodeficiency virus (SIV)-infected rhesus macaques have shown that chronic alcohol consumption promotes a prooxidative and proinflammatory skeletal muscle milieu in SIV-infected animals, and this is associated with accentuated wasting at end-stage SIV infection (21,24). The inflammatory environment in skeletal muscle would be expected to activate quiescent SCs to proliferate and differentiate into myotubes to compensate for enhanced skeletal muscle proteolysis (39,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The detrimental impact of chronic alcohol abuse on skeletal muscle mass balance is further accentuated in diseased states. Studies from our group have demonstrated that chronic alcohol consumption markedly exacerbates the end-stage muscle wasting in a simian immunodeficiency virus-infected rhesus macaques (78), and this is the result of an inflammatory, oxidative milieu that promotes dysregulation of the ubiquitin proteasome pathway (67).…”
Section: Impact Of Alcohol On Body Compositionmentioning
confidence: 99%